Comercio exterior y estructuras productivas en América del Norte - Aroche-Reyes, Fidel (2001)
This paper evaluates the role that the external sector plays in the US and Mexican economic structures in the perspective of the integration process as found about the time the North American Free Trade Agreement was signed. Thus the paper pursues finding indicators for the integration levels between these two economies in the 1990's. The method of analysis relies upon the Input-Output model. Results suggest that those economies maintain an asymmetric relationship concerning the nature of their bilateral trade, e.g., the weight of that exchange in the total foreign trade is quite different. Nevertheless, these economies show striking structural similarities, which explain the parallel role that trade plays in each country, despite the obvious differences in the importance of the external sector in each economic structure.